An integrated drilling, protection and sealing technology for improving the gas drainage effect in soft coal seams. (November 2020) - Li, Hong; Wang, Wei; Liu, Yanwei; Ma, Jinkui; Gao, Hong
Abstract: There are many problems within drilling in soft and broken coal seams, such as borehole collapse, borehole air leakage, CO Toxic gas generated during borehole construction, coal dust pollution to the working environment and other hazards. The efficiency of coal seam gas drainage can be seriously affected by the above problems. To solve these problems, an integrated drilling, protection and sealing (IDPS) technology is proposed for borehole construction. Four major technologies are integrated: the high-purity nitrogen as slag discharge medium is used for the long-distance drilling; the integrated screen pipe inserting technology is adopted to achieve the purpose of borehole protection in the whole drilling process; the new airbag grouting technology guarantees high-quality borehole sealing; and the dust collection device is utilized to realize safe and clean operation environment. The new technology proposed in this study have the following five advantages in such as: long-distance drilling in soft coal seams, borehole protection in the whole drilling process, high-quality borehole sealing, a dust-free and safe operation environment, and efficient gas drainage. The application of IDPS technology in Hudi Coal Mine shows that the problems such as difficult borehole formation, poor gas drainage effect and coal seam outburst risk in soft and broken outburst coal seam can be effectively solved. Meanwhile, the IDPS technology proposed in this study provides scientific guidance for gas drainage in soft and broken coal seam. Highlights: A comprehensive security technology for long-distance drilling in soft and broken coal seams, full-hole long guard holes, high-quality sealing holes, and cleaning operations and efficient extraction is proposed. The directional rig and slag discharge as nitrogen subsystem achieve long-distance drilling while avoiding carbon monoxide poisoning accidents. Protection and sealing borehole subsystem realizes the effect of long hole protection and tight hole sealing. Dust capture subsystem achieves clean working environment. The safety protection subsystem guarantees the safety of site operators and the gas concentration does not exceed the limit.